Entre a proposição e a crítica: o Partido dos Trabalhadores e as políticas públicas em educação: Vila Velha (1989-1996), Vitória e Cariacica (1993-1996) - Melo, Douglas Christian Ferrari de (2007)
Antônio Gramsci provided the theorical basis for this research which concluded that Worker´s Party councilman passed from a collective being to an individual one. Thus, most Worker´s Party councilmen, except for whose who were educators, did not consider the education one of their main issues – mainly during the elaboration of their law projects. This so happens that when Worker´s Party councilmen due to their opposing situation, end up fiscalizing more than legislating. This is the result of not having education as a priority action caused by lack of knowledge and/or support. Another reason was the correlation of forces that made the project presentation really difficult, and even sometimes discouraging. In other hand, the councilmen acted according to left and democratic way. Therefore, whenever that were project concerning education appeared in the project by the other party councilmen, those who belong to Worker’s Party did not hesitate to support it, showing clearly in this attitude the colletive usconscious. 20 Paraphrasing Plekânov, we should to consider the importance of individual in politics. Considering this research, we suggest that the party changes its way of actuating, since that one of huge difficulties is the fact there are not public policies, elaborated and systematized, which really represents the party. Most times, this absent of public policies can be a sign of no internal discussions as an opposing group. So, the groups called Setoriais could be resignified. Nowadays, those groups are divided in social and professional categories (trade union, youth, agrarian, woman), however it could be reorganized according to different areas of public policies: education, health, public security, among others.